ANALISIS PENGARUH NON-TARIFF MEASURES EKSPOR KOMODITI CRUDE PALM OIL (CPO) INDONESIA KE NEGARA TUJUAN EKSPOR UTAMA - Ayu Renita Sari; Dedi Budiman Hakim; Lukytawati Anggraeni (IPB University, 2014)
The study of this paper is aimed to evaluate the effects of non-tariff measures (NTM) upon Indonesian crude palm oil (CPO) export in the main destinations. Identified the competitiveness analysis using the Revealed Comparative Advantage index and the impact of the measures has estimated using a panel data gravity model constructed with disaggregated data about bilateral export trade flow of crude palm oil between Indonesia and its main trade partners for the period from 2003 to 2013. NTM represented binary variable that specified with a dummy variable. The gravity model has estimated with a fixed effects model and the results indicated that the existence of trade barriers to trade (TBT) appears to impede the Indonesian exports of CPO. But the existence of sanitary and phytosanitary measures (SPS) which related to food safety and the existence of trade remedy (antidumping, subsidy, safeguard) presented a positive impact upon the Indonesian exports of CPO. Keywords: Export, Non-Tariff Measures (NTM), Sanitary and Phytosanitary (SPS), Trade Barriers to Trade (TBT), Trade Remedy, Crude Palm Oil